Developing English Learning Materials for Accounting Students: Language Challenges and Accounting Education - Refa'i Refa'i (Journal of English Education and Entrepreneurship (JEEP), 2023)
This study explores the relationship between language challenges and accounting education in the S1 AccountingProgram at Universitas Muhammadiyah Metro. Using a meticulous mixed-methods approach involving language assessments, surveys, and focus group discussions, the research examines students' perceptions of language barriers. The findings emphasize the role of tailored English learning materials in addressing these challenges, enhancing language proficiency, and boosting students' confidence in comprehending complex accounting content.Collaboration between language instructors and accounting experts is highlighted as a key factor in achieving effective integration. The study also underscores the broader relevance of this approach, aligning with the evolving demands of the global business landscape and improving students' employability. The study offers practical recommendations for institutions, students, educators, and researchers to address language challenges holistically and foster specialized discipline proficiency. By implementing these suggestions, stakeholders can bridge the language-discipline gap and cultivate graduates skilled not only in their chosen field but also in effective cross-disciplinary communication. Ultimately, this research contributes to the discourse on integrating language and specialized education, presenting practical avenues for implementation.